Michael Allen's guide to e-learning : - Allen, Michael W. (Wiley, 2016)
Explore effective learning programs with the father of e-learning Michael Allen's Guide to e-Learning: Building Interactive, Fun, and Effective Learning Programs for Any Company, Second Edition presents best practices for building interactive, fun, and effective online learning programs. This engaging text offers insight regarding what makes great e-learning, particularly from the perspectives of motivation and interactivity, and features history lessons that assist you in avoiding common pitfalls and guide you in the direction of e-learning success. This updated edition also considers changes in technology and tools that facilitate the implementation of the strategies, guidelines, and techniques it presents. E-learning has experienced a surge in popularity over the past ten years, with education professionals around the world leveraging technology to facilitate instruction. From hybrid courses that integrate technology into traditional classroom instruction to full online courses that are conducted solely on the internet, a range of e-learning models is available. The key to creating a successful e-learning program lies in understanding how to use the tools at your disposal to create an interactive, engaging, and effective learning experience.